Agroextrativismo vegetal e obtenção de matéria-prima para o mercado de cosméticos verdes: estudo de caso da cofruta, em Abaetetuba-Pará - MARQUES, Mônica Pereira (2023)
The objective of this work was to carry out a diagnosis, through the application of a questionnaire, to identify the practices employed in agroextractivism of non-timber forest products (PFNM) to obtain raw materials, aiming at the production of green cosmetics, based on the case of Abaetetuba Fruit Growers Cooperative (COFRUTA). As a result, it was noted that the species used for the processing of raw materials for cosmetics are: cupuaçu, andiroba, tucumã, ucuúba, murumuru and patauá. The way cooperative members manage follows organic production protocols, as well as the transport of fruits from the communities obeys the traceability practices of Non-Wood Forest Products (PFNM). In the processing of raw materials, the use of practices that meet the demands of the purchasing companies for the production of cosmetics, for example, Natura, was verified. Although the management and processing of the raw material are carried out according to the standards of organic products, the species in question still do not receive certification. This fact is explained by the high values charged by the certifiers, since great distances need to be covered to monitor the production, which is diverse and occurs in different locations on the islands of Abaetetuba. It is concluded that COFRUTA and its members employ practices in their production stages that enable the commercialization of raw materials for green cosmetics, however, the high values for obtaining the certifying seal is still an obstacle to regularize organic production.